A first assessment of cyanobacterial blooms in oligotrophic Lake Superior. (3rd August 2020) - Sterner, Robert W.; Reinl, Kaitlin L.; Lafrancois, Brenda Moraska; Brovold, Sandra; Miller, Todd R.
Abstract: Lake Superior is often described as the most pristine of the Laurentian Great Lakes, but in the past decade Dolichospermum blooms have been observed. Land use in the adjacent watershed has not changed appreciably during this time, but the lake is warming and climatological variables correspond with presence of blooms. Blooms occurred only in relatively warm years as measured by degree days. Furthermore, the two largest blooms, in 2012 and 2018, occurred during years of especially extreme rainfall, providing coincidental evidence that intense storms provide nutrients or living propagules to the blooms from the watershed. Nearshore lake water in the narrow zone where blooms appear shows some riverine influence compared to water further offshore even in the absence of blooms. Nevertheless, water chemistry associated with the largest bloom in 2018 more closely resembled nonbloom nearshore lake water than river water, suggesting that blooms develop or at least persist outside of distinct river plumes. Concentrations of P and N during peak bloom density greatly exceeded any nonbloom lake or river waters, indicating that a buildup of phytoplankton biomass perhaps by floating and drifting to shore also is a significant factor in bloom occurrence. One potentially toxic substance (Anabaenopeptin A) was observed but at low concentration. At peak phytoplankton concentration, high seston C : P indicated severe P limitation while low C : N pointed against N limitation. If these newly observed blooms are indeed driven by temperature and rainfall as this evidence suggests, blooms may continue.